Ablative and mechanical properties of quartz phenolic composites - Maria L. Gregori; Edson A. Barros; Gilberto P. Filho; Luiz Cláudio Pardini; Sonia F. Costa (Journal of Aerospace Technology and Management, 2009)
Quartz phenolic composites have been applied to thermal protection systems (TPSs) for reentry vehicles since the late fifties due to their excellent ablative resistance and mechanical performance. TPSs must withstand the aggressive reentry environment, such as atomic oxygen, when submitted to very high temperatures (> 1000° C) and heat flux. The ablative performance ofcomposites is influenced by both base materials and environmental parameters during the ablation process. For TPS systems phenolic resin is usually used as the base matrix due to its ability to form a stable char during decomposition. This char plays an important role in the absorption of the heat generated during the ablation process. During re-entry, parts of the charred matrix can be abrasively removed by shear force due to high pressure and velocity. In this work the ablative and mechanical properties of quartz phenolic composites were evaluated in order to identify the range of properties suitable for the use of these materials as thermal protection systems for space vehicles. Quartz fabric having an areal weight of 680 g/m2 and a resole-type phenolic resin were used to prepare the composites. The resin has a viscosity of 165 MPa at 20°C. The prepreg material was cured by heating under pressure of 100 bar in a mold. The resin content of the prepreg obtained was about 50 per cent. The mechanical properties evaluated were, tensile, shear and flexural strength. The results obtained showed that this material has average values of 38.5 MPa, 52 MPa and 85 MPa for tensile, shear and flexural strength, respectively. The ablative tests were carried out in a high-energy air plasma in ambient atmosphere and the mass losses were measured for different exposure time.